Evaluation of Coriander (Coriandrum sativum L.) Genotypes under Normal and Limited Moisture Stress Condition - Singh, Arvind; Singh, Dhirendra; Khedar, O P; Dayanand, Dayanand (Annals of Arid Zone, 2018)
Yield potential of a variety is combined effect of genotype and environment interaction. Among different seed spices, coriander is an important cultivated seed spice crop. In India, majority of this crop is still under limited irrigation and conserved moisture. Drought is very common adverse environmental factor limiting crop production in most of the tropical and subtropical regions of India. To generate information on the effect of moisture stress on various traits which contribute towards yield would be helpful in developing tolerant coriander genotypes. The results revealed that plant height; umbels per plant and biological yield per plant are most important yield components under limited moisture condition. On the basis of overall performance (Stress susceptibility index, SSI), seed yield under stress and stress tolerance index (STI) values, UD-728, RCr-480 and Hisar Anand were identified as potential genotypes for stress condition. The indices, SSI and STI, could be taken as important criteria for breeding of coriander genotypes suitable for stress environments.Key words: Genetic advance, heritability, stress susceptibility index, stress tolerance index, variability.